Algebraic communication channels - V. K. Leontiev; Gh. L. Movsisyan (Institute of Mathematics)
Modern information theory studies various communication channels modelling certain situations. The basic matter of the present research is the information transmission process from а source to а receiver, and main parameters are the throughput/carrier capacity/transmission capacity and the information transmission speed.
Keywords: General algebraic systems